Modélisation de l'affinage de l'huître Crassostrea gigas alimentée avec la diatomée Skeletonema costatum - Meleder, Vona; Barille-boyer, Anne-laure; Baud, Jean-pierre; Barille, Laurent; Cognie, Bruno; Rosa, Philippe (EDP Sciences, 2001)
The traditional fattening of the oyster Crassostrea gigas in oyster ponds of the French Atlantic Coast is submitted to natural environmental fluctuations. In order to reduce the growth variability of the soft parts of the bivalve, an intensive fattening process was developed, where the conditions of temperature, particulate organic and inorganic matter (POM and PIM) are controlled. This process relies on the production of the diatom Skeletonema costatum, which is then distributed to the oysters at an average concentration of 4–5 mg POM·L–1. An ecophysiological model of the oyster C. gigas, which simulates the evolution of somatic and gonad–reserve compartments, was applied to these conditions in order to analyse the bivalve responses. Experimentation was performed to elaborate the model and two functions were studied: clearance rate and pseudofecal production. At a temperature of 14 °C, chosen for the fattening process, and at POM and PIM concentrations varying respectively from 4 to 18 mg·L–1 and 15 to 55 mg·L–1, it was found that clearance rate was not regulated (mean of 2.09 ± 0.11 L·h–1·g–1 with 59% of activity rate) and that ingestion rate depended on the production of pseudofeces. This production allows an increase of organic ingested fraction, by the mechanism of pre-ingestive selection that buffers the PIM variability. Negative effects of PIM on growth have been studied through several simulations. It appears that actual POM ration (4–5 mg·L–1) used in the fattening process, allows dry tissues growth, in spite of simulated PIM concentration up to 50 mg·L–1. The elaboration of the model revealed that gametogenesis is a major determinant in bivalve energy partitioning in the rich food conditions of this fattening process. L’affinage traditionnel des huîtres creuses, pratiqué dans les claires ostréicoles de la façade Atlantique française, est soumis aux fluctuations des facteurs environnementaux. Un procédé d’affinage contrôlé en terme de matières organique et inorganique particulaires (MOP et MIP) et de ...